Investigating a collaborative approach to peer feedback. (23rd February 2019) - Alshuraidah, Ali; Storch, Neomy
Abstract: This paper reports on the first phase of our research into the potential merits of a collaborative writing/feedback/revision activity. The study compared the quantity and quality of the feedback provided, collaboratively and individually, by adult EFL learners in Saudi Arabia. Our analysis showed that learners provided more feedback, including more constructive comments, in the collaborative format. Most of the students also felt that providing feedback in pairs alleviated some of their concerns about providing feedback individually on their peers' writing. We suggest that the combination of collaborative writing and feedback may improve peer feedback and provide learners with enhanced language learning opportunities.